The Characteristics of Thunderstorms and Their Lightning Activity on the Qinghai-Tibetan Plateau - Lei Hui; Yunjun Zhou; Zhitao Yan (Advances in Meteorology)
This paper discusses the temporal and spatial distribution characteristics of cloud-to-ground (CG) lightning activity over the Qinghai-Tibetan Plateau (QTP) from 2009 to 2018 and their dependence on meteorological factors. It is found that (1) the number of CG flashes fluctuates, reaches a maximum in 2014, and then gradually decreases. The main active period of CG lightning is from June to September each year, after which it decreases rapidly. CG lightning is mainly distributed in the valley areas at around 4800 m above sea level at Lhasa, Nagqu, and Chamdo, and there are differences in the characteristics of CG activity in these three areas. The peak of daily CG lightning occurs at 1000 UTC, and the lowest value is at 0400 UTC. The distribution of CG lightning in all seasons has obvious differences in peak time and the proportion of positive CG (+CG) lightning, with the ratio of +CG lightning to total CG lightning flashes in spring and autumn exceeding 50%. (2) The ratio of +CG lightning to total CG lightning flashes over the QTP is influenced by a combination of thermodynamic and microphysical factors. Over the QTP, greater vertical wind shear leads to the movement of upper positive charges and promotes the occurrence of +CG lightning. Also, the higher total column liquid water content implies higher cloud water content in the warm-cloud region, and the higher cloud-base height implies a thicker warm-cloud region, which is not conducive to the occurrence of +CG lightning. (3) During high-value years (in this study, 2010, 2012, 2014, and 2016), the midlatitude (30°N–60°N) high pressure is strong and the plateau is situated at the intersection of the East Asian and South Asian monsoons and the cold air from the northwest, which strengthens the water vapor convergence and increases the frequency of thunderstorms. When the plateau is under the control of the southerly monsoon from June to September every year, its atmosphere is full of water vapor and lightning activity is accordingly high, with the proportion of +CG lightning being about 10%. Meanwhile, in the remaining months, when controlled by the westerly wind belt, the plateau’s water vapor condition is poor, the level of lightning activity weakens, and the proportion of +CG lightning gradually increases to more than 50%.